Regulation and function of the cyclic nucleotide phosphodiesterase (PDE3) gene family - Shakur, Yasmin; Holst, Lena Stenson; Landstrom, Tova Rahn; Movsesian, Matthew; Degerman, Eva; Manganiello, Vincent (Progress in Molecular Biology and Translational Science, 2001)
This chapter discusses some general information about cyclic nucleotide phosphodiesterases (PDEs). It also discusses the PDE3 gene family, emphasizing the molecular biology, structure/function relationships, and cellular regulation and functional roles of PDE3s, as well as physiological/pharmacological actions, therapeutic applications, and potential benefits of PDE3 inhibitors. The major cause of concern in the use of PDE3 inhibitors as therapeutic agents is the potential for increased mortality in patients with known heart disease. Although caution is certainly warranted in this context, conclusions should not be indiscriminately applied to all PDE3 inhibitors. The pharmacological profiles of newer PDE3 inhibitors differ from those of the PDE3 inhibitors used in earlier heart failure clinical trials. Although milrinone and cilostazol are similar in potency as inhibitors of PDE3, milrinone had greater effects than cilostazol on increasing both cyclic adenosine monophosphate (cAMP) and contractility in isolated rabbit cardiomyocytes. The ability to target PDE3 inhibitors to specific isoforms in specific intracellular compartments and/or specific cells may be critical for improvement in efficacy and safety. The acute benefits and chronic adverse actions of PDE3 inhibitors in patients, with heart failure, may result from the phosphorylation of different substrates of Protein kinase A (PKA) in different intracellular compartments. Newer PDE3 inhibitors that target a specific isoform in the appropriate compartment could potentially confer beneficial hemodynamic effects without adverse effects on mortality.